2021
DOI: 10.3389/fonc.2021.764946
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetric Comparison of Helical Tomotherapy, Volume-Modulated Arc Therapy, and Fixed-Field Intensity-Modulated Radiation Therapy in Locally Advanced Nasopharyngeal Carcinoma

Abstract: ObjectiveTo compare the dosimetric parameters of different radiotherapy plans [helical tomotherapy (HT), volume-modulated arc therapy (VMAT), and fixed-field intensity-modulated radiation therapy (FF-IMRT)] for locally advanced nasopharyngeal carcinoma (NPC).MethodsA total of 15 patients with locally advanced NPC were chosen for this retrospective analysis and replanned for HT, VMAT, and FF-IMRT. The prescribed planning target volume (PTV) dose for the primary tumor and metastatic lymph nodes was 70 Gy (2.12 G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 39 publications
(37 reference statements)
0
8
0
Order By: Relevance
“…It is worth mentioning that most of the previous dosimetric studies make dosimetric comparisons by regenerating a VMAT/ tomotherapy plan on the same patient with an existing tomotherapy/VMAT plan, which makes comparisons of clinical outcomes infeasible (4)(5)(6)(7). The current study compared the dosimetric parameters between patients who received tomotherapy and those who received VMAT directly, using PSM to control the balance of confounding factors that may affect dosimetry.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth mentioning that most of the previous dosimetric studies make dosimetric comparisons by regenerating a VMAT/ tomotherapy plan on the same patient with an existing tomotherapy/VMAT plan, which makes comparisons of clinical outcomes infeasible (4)(5)(6)(7). The current study compared the dosimetric parameters between patients who received tomotherapy and those who received VMAT directly, using PSM to control the balance of confounding factors that may affect dosimetry.…”
Section: Discussionmentioning
confidence: 99%
“…In the treatment of NPC, previous studies have shown that tomotherapy is superior or equivalent to VMAT in most dosimetric parameters, including the dose coverage of target volumes and the protections of the spinal cord, brainstem, temporal lobes, and parotids. On the other hand, VMAT has been reported to have significant advantages in shortening treatment time and protecting optic nerves and optic chiasm (4)(5)(6)(7). Besides, the hybrid IMRT/VMAT, which combines IMRT and VMAT, has shown the potential benefit of improving the dose distribution by increasing the freedom to find the optimal combination of angular sampling and intensity modulation (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…HT delivers highly conformal dose distributions for head and neck cancer with an impressive ability to spare critical organs [6,7]. Compared to VMAT and IMRT in patients with NPC, HT presents a sharp dose gradient associated with optimal conformity, homogeneity, and better performance in sparing surrounding organs at risk (OARs) [5]. e dwindling 5-year incidence of TLN in NPC patients treated with IMRT is significantly higher than that in NPC patients treated with conventional RT, by 20% [8].…”
Section: Introductionmentioning
confidence: 99%
“…Intensity-modulated radiotherapy (IMRT) is a modern technique of RT for NPC. Volume-modulated arc therapy (VMAT) and helical tomotherapy (HT), image-guided arc radiotherapy techniques, are receiving additional attention compared with conventional IMRT for patients with NPC [ 5 ]. HT delivers highly conformal dose distributions for head and neck cancer with an impressive ability to spare critical organs [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation